An Investigation into the Different Hardening Models in Reverse Forming of Thin Sheets. (16th November 2009) - Kadkhodayan, M.; Mosayebi, J.
Abstract : This paper discusses a finite element analysis of the Bauschinger effect in the reverse cup drawing process, taken from the NUMISHEET'99 (Gelin and Picart, 1999) benchmark. In order to study the Bauschinger effect, several hardening models are considered such as isotropic, kinematic, and combined forms in the linear and nonlinear cases, including the well-known Yoshida and Chaboche's model. The obtained results have been compared with some experimental results reported in literature. The various factors, namely, normalized axial stress, von Mises stress, and the punch forces, for both first and second stages have been calculated for different materials and thicknesses. Results show that the combined model had acceptable agreement with the empirical data through both stages, while the bilinear models did not show this effectiveness. Generally, the nonlinear kinematic and combined models lead to more accurate results.